Coordinate reference systems for high precision geodesy - Whitmore, Guy Matthew (1994)
The advent of the Global Positioning System (GPS) meant that, for the first time, the geodetic and geophysical community has a tool for measurements on a global, continental and national scale. Global GPS networks are already competing with VLBI and SLR for the measurement of inter-continental baselines and earth rotation parameters. The development of the 'high accuracy fiducial GPS technique', as described in this thesis, has produced results comparable with mobile VLBI and SLR systems, but in shorter observational periods and at lower costs. Combined with global GPS networks, which have the potential to provide time-tagged fiducial station coordinates at the observational epochs, coordinates can be determined in a global reference frame. The results in this thesis, from a fiducial GPS campaign to monitor the vertical land movement at tide gauge sites in the UK, demonstrate that millimetric precisions and accuracies can be obtained in all three components over baselines of hundreds of kilometers. The combination of GPS with existing 2-d classical triangulation networks for mapping, engineering surveying and navigation has caused many problems, since the GPS observations are 3-d and of a superior quality. In Europe these problems have been overcome by the establishment of a new high precision reference framework, EUREF, based on fiducial GPS carried out in 1989. This thesis also describes the determination of coordinates for the UK EUREF stations and their application for geodetic control in Great Britain.